LncRNA CCAT2 promoted osteosarcoma cell proliferation and invasion. Issue 5 (4th March 2018) - Yan, Lihua; Wu, Xiangkun; Yin, Xianzhe; Du, Feng; Liu, Yongxi; Ding, Xunmeng
Abstract: Long non‐coding RNA (lncRNA) plays important roles in tumour progression. Accumulating studies demonstrated that lncRNA colon cancer‐associated transcript 2 (CCAT2) acted as an oncogene in many tumours. However, the role of CCAT2 in the development of osteosarcoma has not been elucidated. In our study, we indicated that CCAT2 expression was up‐regulated in osteosarcoma tissues and cell lines (SOSP‐9607, MG‐63, U2OS and SAOS‐2). In addition, osteosarcoma cases with higher CCAT2 expression had a poorer disease‐free survival and shorter the overall survival time compared to those with lower expression. Overexpression of CCAT2 promoted osteosarcoma cell proliferation, invasion and cell cycle. Furthermore, ectopic expression of CCAT2 increased the expression of mesenchymal markers N‐cadherin, vimentin and snail and reduced the expression of N‐cadherin marker E‐cadherin. CCAT2 overexpression promoted the LATS2 and c‐Myc expression in osteosarcoma cell. These data indicated that CCAT2 served as an oncogene in osteosarcoma and promoted osteosarcoma cell proliferation, cell cycle and invasion.